Neck circumference: Independent predictor for overweight and obesity in adult population - Madhur Verma; Meena Rajput; Soumya Swaroop Sahoo; Navjot Kaur (Wolters Kluwer Medknow Publications, 2017)
Background: Neck circumference (NC) measurement, an index of upper body fat (BF) distribution, seems promising as a community-based screening measure for overweight and obesity in want of evidence on its validity as a screener. Objective: The objective of this study was to determine the validity of NC as a screener for overweight and obesity in adults in community settings against BF percentage (BF%). Materials and Methods: This cross-sectional community-based study involved data collection on a predesigned, pretested, and semi-structured schedule that included the sociodemographic characteristics and anthropometric measurements of respondents. Results: NC correlated positively with body weight, waist circumference, and hip circumference. NC was found to have good discriminatory power with cutoff values of 36.55 cm for males and 34.05 cm for females, with maximum sensitivity and specificity to predict overweight and obesity in comparison to direct BF% estimation on receiver operating characteristic analysis. Conclusion: NC has a fair validity as a community-based screener for overweight and obese individuals in the study context. Further studies may be carried out to explore the generalizability of this observation.